Palliative MRI-guided transurethral ultrasound ablation for symptomatic locally advanced prostate cancer - Mikael Anttinen; Pietari Mäkelä; Pertti Nurminen; Eemil Yli-Pietilä; Visa Suomi; Teija Sainio; Jani Saunavaara; Pekka Taimen; Roberto Blanco Sequeiros; Peter J. Boström (TAYLOR & FRANCIS LTD, 2022)
Purpose Locally advanced prostate cancer can cause bladder outlet obstruction, gross hematuria and frequent hospitalization. While these complications are commonly treated by palliative transurethral resection of the prostate, the improvement is often insufficient. The purpose of this study was to evaluate the safety and feasibility of MRI-guided transurethral ultrasound ablation as an alternative palliative treatment option (pTULSA) for men suffering from symptomatic locally advanced prostate cancer.
Methods This prospective, phase one study included 10 men in need of palliative surgical intervention due to urinary retention and gross hematuria caused by locally advanced prostate cancer. Patients were followed for 1 year at 3-month intervals. Time without catheter, time without hematuria, reduction in hospitalization time, and adverse events were measured.
Results Ten patients with locally advanced prostate cancer were enrolled, all having continuous catheterization due to urinary retention and nine had gross hematuria before treatment. At 1 week post-pTULSA five patients were catheter-free. At last follow-up catheter-free and gross hematuria-free rates were 70% and 100%, respectively. Average hospitalization time from local complications reduced from 7.3 to 1.4 days in the 6 months before and after pTULSA. No > Grade 2 treatment related adverse events were reported, with all five being urinary tract infections.
Conclusions pTULSA appears safe and feasible for palliative ablation of locally advanced prostate cancer. The therapy seems to accomplish long-term hematuria control, can relieve bladder outlet obstruction in selected patients, and seems to reduce the burden of hospitalization due to local complications.